INORGANIC WASTE BINS TO INCREASE COMMUNITY PARTICIPATION IN MANAGING HOUSEHOLD WASTE - Kurniawan, V. Reza Bayu; Sulistyorini, Dewi; Gutama, Detha Sekar Langit Wahyu; Wibowo, Robertus Anggi Candra; Pasaribu, Wandoni; Purnomo, Haryo (Transpublika Publisher, 2024)
The increase in population significantly impacts the growth of waste volume. In Indonesia, poor waste management exacerbates the issue of waste. In Yogyakarta, specifically, this problem has become critical due to the permanent closure of the integrated waste disposal site that has been relied upon. Despite various government programs being implemented, the active participation of the community as waste producers in addressing waste issues must be continuously enhanced. Independent waste management is one of the frequently proposed solutions. This program is supported by an overarching program called the waste bank. The existence of the waste bank must be accompanied by a high level of community participation. However, the lack of community access to the waste bank needs attention. Accordingly, this community service program will provide inorganic waste bins to increase community participation in managing inorganic waste while supporting the role of the waste bank. There are two main activities in this program: the design and production of inorganic waste bins, and the community education of household waste management. This community service collaborates with the waste bank located in Muja-Muju, Yogyakarta, targeting the campus area of the Faculty of Engineering at UST and the community on Miliran Street. This initiative also involves cooperation between the campus and the bank in institutional-scale waste management.